Visulization of the flow over disc-wing - Potts, J. R.; Crowther, W. J. (9. International Symposium on flow visualization, 2000)
An experimental investigation into the flow characteristics of a disc-wing has been carried out in a low speed wind tunnel over a flow speed range of 0 to 20 m/s. The disc-wing considered has an axi-symmetric, approximately elliptic cross-section and hollowed out underside cavity. The aim of this research was to gain an understanding of the complex three-dimensional flow structures, in order to identify regions receptive to flow control technologies such as vortex generators or synthetic (massless) jets. Flow visualisation techniques including surface paint and smoke wire methods have been utilised to determine the position and form of surface flow structures.